Screening of Pigeonpea Genotypes Against Pod Borer Complex - R. M. Jalondhara; D. R. Patel; Alok Shrivastava (International Journal of Economic Plants)
Field screening of 15 genotypes and cultivars against pod borer and pod fly showed that among 15 genotypes and cultivars, BDN-2, GT-1 and GAUT-93-17 were less infested by pod borer and pod fly and gave higher yield. No correlation was observed between morphological plant characters of pigeonpea and pod borer and pod fly infestation.